2007
DOI: 10.1093/jxb/erm209
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the UDP-glucose dehydrogenase gene family in Arabidopsis, a key enzyme for matrix polysaccharides in cell walls

Abstract: Arabidopsis cell walls contain large amounts of pectins and hemicelluloses, which are predominantly synthesized via the common precursor UDP-glucuronic acid. The major enzyme for the formation of this nucleotide-sugar is UDP-glucose dehydrogenase, catalysing the irreversible oxidation of UDP-glucose into UDP-glucuronic acid. Four functional gene family members and one pseudogene are present in the Arabidopsis genome, and they show distinct tissue-specific expression patterns during plant development. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 42 publications
5
94
1
Order By: Relevance
“…The alkaline pH optimum for EsGMD1 is approximately pH 8.5-and thus near to the pK a -value of the Cys residue. Similar pH optima were observed for UGDs from plants (17,18). For the Pseudomonas GMD Roychoudhury et al (9) report a significantly lower and very sharp pH optimum of pH 7.7 which seems to be an exception for this group of enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…The alkaline pH optimum for EsGMD1 is approximately pH 8.5-and thus near to the pK a -value of the Cys residue. Similar pH optima were observed for UGDs from plants (17,18). For the Pseudomonas GMD Roychoudhury et al (9) report a significantly lower and very sharp pH optimum of pH 7.7 which seems to be an exception for this group of enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…PIF4 may also be involved in auxin signaling as shown by the lack of induction of the auxin-inducible IAA29 UDP-glucuronic acid, from which it is estimated that in Arabidopsis 50% of cell wall biomass is derived. 10 We found that four UDPG dehydrogenases (UDPG-DH) genes which form UDP-glucuronic acid from UDPG were upregulated by T6P ( Table 1, Fig. 2).…”
Section: Light and Auxin Signaling Are Involved In The Growth Responsementioning
confidence: 90%
“…These enzymes are tightly correlated with cell division and growth. 10 In trees they are used as a marker enzyme for cambial meristem. Three UDP-glucuronic acid decarboxylases which form xylose from UDP-glucuronic acid and a UDP-xylose epimerase which forms xylose from arabinose were also upregulated, together with two glucuronic acid epimerases which catalyze formation of UDP-galacturonic acid and a rhamnose synthase.…”
Section: Light and Auxin Signaling Are Involved In The Growth Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, two UDP-glucose dehydrogenase (UGD) genes that encode important enzymes in the synthesis of pectins and hemicelluloses were also activated in the transgenic plants. Expression of UGD genes is typically restricted to growing cells (Johansson et al, 2002;Klinghammer and Tenhaken, 2007).…”
Section: Cell Wall Modificationmentioning
confidence: 99%